Pediculosis Capitis with Complication Sepsis and Anemia In Elderly Patient: A Case Report - Rahmadewi Rahmadewi; Riyana Noor Oktaviyanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2019)
Background: Pediculosis is an ectoparasitic infestation of human scalp. Infestation is characterized by intense itching, secondary infection, and anemia in cases of severe infestation, and inadequate diet. Treatment of head lice includes physical methods, topical pediculicides, and oral agents. Purpose: To report a case of pediculosis capitis with complication of sepsis and anemia in elderly patient Case: A women, 80 year-old, body weight 45 kilograms, came to Emergency Room of Dr. Soetomo General Hospital with complaint about malaise, low appetite, and sometimes fever since 1 week ago. Patient also complained about itchy sensation on her scalp appeared since 3 months ago. There were many lices on her scalp. Itchy sensation was felt all day. Patient took a bath only once daily, and spent her time on bed because patient had a hemiparese since 6 months ago. History of the same disease in the family, her grandson also had the same complaint (lice on scalp). No history of bleeding or gastrointestinal bleeding. Patient had a low appetite. There were so many lices on her scalp, with erosion and crustae. Patient was treated with systemic antibiotic ceftriaxone injection 2 times 1 gram daily, metronidazole drip 3 times 500 mg, Packed Red Cell (PRC) transfusion 2 kolf /day until Hb more than10 g/dl, permethrin 1 % (Peditox). The treatments gave a good result. Discussion: Head-to-head contact is by far the most common route of lice transmission. We assumed that the infestation could stem directly from hair in hair contact, or indirectly, e.g. towels, which may have been already used by infected people. The source of contagious in this case could be from her grandson who also had the same complaint (lice on scalp). Treatment of pediculosis is permethrin 1%, other options if these treatments don’t work include malathion, benzyl alcohol, spinosad, and topical ivermectin. Conclusion: This patient was successfuly treated with permethrin 1 % (Peditox) and repeated treatment after 7 days gave good results and in this case there were no side effects. Patient education is the key in preventing pediculosis capitis and also reminding patients that they can help to prevent the spread of these parasites.